ANALYZING SOCIALLY RESPONSIBLE CONSUMPTION IN INDONESIAN CUSTOMERS BEHAVIOR - Maria Ulfah Catur Afriasih (Jurnal Ilmiah Publipreneur, 2021)
ABSTRACT                                                              The dominance of foreign products for environmentally friendly products in Indonesia can be seen from the large market share of foreign products. This creates a tendency for emotional factors, namely consumer behavior, to affect what they buy and will therefore create a sense of social responsibility for consumers when consuming a product. This will also have an impact on the level of customer loyalty, and the impact is very positive; they will repurchase. This study was conducted to raise five important issues, namely: how is the picture of consumer behavior and socially responsible consumption formed?. The research method used is the descriptive method. As many as 100 consumers were sampled in a several month. The sampling techniques Descriptive and explanatory surveys are commonly utilized. The method examines data was making use of path analysis. Based on the results, it can be concluded that there is a fairly high influence between customer behavior and socially responsible consumption, which means that the three variables have a strong correlation. As a result, the corporation must educate and socialize the public about the necessity of green cosmetics that bring greater benefits.Keyword: SRC, green consumption, customer behavior